Utilization of Acid – Acid Power Plant Fly Ash Waste as a Partial Substitute for Cement for Structural Concrete Manufacture In Terms of Cost Efficiency - khairil yanuar; Suwaji Suwaji; Ria Adriyati; Rezky Anisari; Rinova Firman Cahyani; Adriani Muhlis; Abdul Hafizh Ihsani; Aldo Hermaya Aditiya Nurkarsa (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The production of fly ash from pltu Asam - Asam waste is quite a lot, which is approximately 80 tons per day, so it is necessary to develop its utilization. This study aims to determine the extent of the effect of water use on the fly ash mixture and the extent to which fly ash can be used as a substitute for part of cement and take into account the cost efficiency in the production of concrete mixture per m3. The results showed that the addition of fly ash can reduce water use from the planned amount of water, but the ease of work remains good (workability). The production cost of 1 m 3 of mixed concrete is 15%, 30% fly ash is 8.13% cheaper and 16.27% cheaper on average compared to normal concrete production costs, this shows that the use of fly ash as a substitute for part of cement can reduce the production cost of concrete/m3